Improving farmers’knowledge through empowerment training on smart irrigation systems in hydroponic farming - Budi Herdiana; Jana Utama; Muhammad Aria Rajasa Pohan; Rodi Hartono; Tri Rahajoeningroem; Bobi Kurniawan Soegoto; Sri Supatmi; Yusrila Yeka Kerlooza (University of Merdeka Malang, 2025)
Managing irrigation systems in hydroponic based farming models is one of the main challenges currently being faced. The existing issue lies in the lack of accuracy and precision in providing the appropriate levels of nutrients and water to the plants. This leads to a decline in the quality of vegetable products, highlighting the urgent need to strengthen knowledge and skills in operating intelligent technology-based irrigation systems for vegetable growers. Therefore, the proposed training program based on interactive, collaborative, and practical approaches in this community service activity is a strategic step to address the partners' problems, focusing on enhancing the skills and understanding of plantation workers and the surrounding community, which is the primary goal of this activity. The training method emphasizes hands-on field practice, using pre-test and post-test results as references for developing the training materials. The results showed an increase in participants' understanding, as indicated by an average score improvement of 70.8 percent, with a total of 15 respondents. This indicates that the training was effective in improving participants' understanding and skills in using intelligent technology-based irrigation system devices.